Efficacy of intravitreal dexamethasone implant in patients with Vogt–Koyanagi–Harada Disease and bilateral panuveitis: Two case reports. Issue 40 (8th October 2021) - Chen, Po-Lin; Chen, San-Ni
Abstract: Introduction: Vogt–Koyanagi–Harada (VKH) disease is a multisystemic disorder characterized by intraocular inflammation associated with serous retinal detachment, optic disc edema, uveitis, and vitritis, and is often associated with neurologic and cutaneous manifestations. Diagnosis can be assisted by fluorescein angiography and optical coherence tomography that can help evaluate changes in the retina. Therapy relies mainly on the use of corticosteroids, administrated through oral or intravenous high-dose pulses, and immunosuppressants. The purpose of our study was to assess the outcome of VKH disease with bilateral panuveitis treated with dexamethasone intravitreal implant. Patient concerns: Two patients without underlying disease had severe vision deterioration, eye pain, following flu-like symptoms. Diagnosis: At initial diagnosis, macular edema and sub-retinal fluid lobulated accumulation were noted under SD-OCT exam. FAG revealed multiple pinpoint leakage around macula and pooling of dye within sub-retinal space. Interventions: All two patients received intravenous pulse methylprednisolone at the diagnosis, followed by oral prednisolone and cyclosporine. One patient received bilateral eye dexamethasone intravitreal implant two weeks after diagnosis, while the other received left eye dexamethasone intravitreal implant at the time of diagnosis. Outcomes: Vision and macular structure recovered more rapidly after receiving dexamethasone implants in the short-term follow-up. All macular structures recovered to normal, and vision recovered to 20/20 in both eyes. One patient, receiving bilateral dexamethasone implant, didn't relapse during the 13-month follow-up; the other, receiving left eye dexamethasone implant, didn't relapse during the 6-month follow-up. None of them required intravenous high-dose steroids again. Conclusion: VKH disease is a multisystemic disorder; intravenous pulse steroid therapy and oral prednisolone can control systemic inflammation. In addition to systemic prednisolone treatment of VKH disease in the acute phase, dexamethasone implants can enhance short-term and long-term control of intraocular anti-inflammation.